Selection factors that influencing demand on family takaful among the residents in Tampin, Negeri Sembilan / Mardhiah Abu Samah - Abu Samah, Mardhiah (2016)
Family Takaful is one of the service sectors that are expected to continue the growth of economy. The product based on shariah rules for general insurance provided by Insurance Company in Malaysia Therefore,the family Takaful market continues to playmain role in supporting economic and social development rather than other takaful product like General Takaful. Further to this, Malaysia is recorded to be the major player and one of the fastest Takaful growths in Southeast Asia. Therefore, the aim of this paper is to examine the selection factors that influencing demand on family Takaful among the residents in Tampin,Negeri Sembilan. There are several factors that influence selection of family Takaful which religious adherence, perception and image, product and services and marketing and advertising. The respondents are the residents in Tampin, Negeri Sembilan. The study will use a quantitative method were the primary data collection will be through survey questionnaire and secondary sources such as journal and internet. Then, data analysis involves the use method of data analysis such as regression analysis, correlation and others. So, from a set of factors that contributed to the family Takaful demand in this study, based on th result of regression analysis showed that religious adherence and marketing and advertising the critical factors that influence family Takaful demand among the residents in Tampin, Negeri Sembilan.